2009
DOI: 10.1371/journal.pone.0004679
|View full text |Cite
|
Sign up to set email alerts
|

Mating First, Mating More: Biological Market Fluctuation in a Wild Prosimian

Abstract: In biology, economics, and politics, distributive power is the key for understanding asymmetrical relationships and it can be obtained by force (dominance) or trading (leverage). Whenever males cannot use force, they largely depend on females for breeding opportunities and the balance of power tilts in favour of females. Thus, males are expected not only to compete within their sex-class but also to exchange services with the opposite sex. Does this mating market, described for humans and apes, apply also to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 52 publications
3
45
1
Order By: Relevance
“…However, in E. fulvus (this study), and in Propithecus verreauxi (Palagi et al 2008) reconciliation levels did not vary as a function of the sex class combination of the former opponents. This result could be linked to the fact that both studies included the mating period, when male-female bonding increases as a result of the biological market effect (Norscia et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, in E. fulvus (this study), and in Propithecus verreauxi (Palagi et al 2008) reconciliation levels did not vary as a function of the sex class combination of the former opponents. This result could be linked to the fact that both studies included the mating period, when male-female bonding increases as a result of the biological market effect (Norscia et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Ants choose aphids producing the highest quality of honeydew and remunerate them with high-quality protection services (15,25). Similarly, in primate-mating markets, males that offer more grooming are rewarded with more mating opportunities (13,26). Such economic partner discrimination is the key factor driving market dynamics (24,27) and distinguishes biological markets from traditional two-party, direct-reciprocity models (28).…”
Section: (Iii) Choosing and Switching Partnersmentioning
confidence: 99%
“…1) The intrinsic value of each partner depends on alternative commodities it may have to offer. In the case of adult females the strongest fluctuations are probably due to changes in the reproductive cycle: the presence of newborns (Fruteau et al 2011b;Gumert 2007a;Henzi and Barrett 2002;Slater et al 2007) and willingness of males to offer grooming in exchange for sex (Barelli et al 2011;Gumert 2007b;Norscia et al 2009). Further fluctuations may be due to changes in dominance status and the resulting changes in value of agonistic support and tolerance near resources.…”
Section: Which Game Do Grooming Primates Play?mentioning
confidence: 99%
“…The leverage of an individual will depend on its rank, but also on the supply and demand ratio of grooming as well as of commodities exchanged against grooming at the moment the interaction takes place. Many studies of grooming patterns in nonhuman primates have found such effects on grooming patterns (Barelli et al 2011;Barrett et al 1999;Chancellor and Isbell 2009;Fruteau et al 2011a;Ginther and Snowdon 2009;Gumert 2007b;Lazaro-Perea et al 2004;Löttker et al 2007;Norscia et al 2009;Payne et al 2003;Port et al 2009;Slater et al 2007;Tiddi et al 2010;Wei et al 2012;Xia et al 2012Xia et al , 2013. A well-studied example is the exchange of grooming for permission to handle a mother's infant.…”
Section: Introductionmentioning
confidence: 99%